2021
DOI: 10.24252/bio.v9i2.22232
|View full text |Cite
|
Sign up to set email alerts
|

Effect of biofertilizer on growth and metaxylem diameter of Amaranthus tricolor L. in salinity stress condition

Abstract: Throughout history, agricultural sector in Indonesia has faced a shortage of land. As a result, we must take use of land that is still available, even if the conditions are unsuitable for plant growth, one of which is salinity-stressed land. Amaranth is a frequently cultivated plant in Indonesia (Amaranthus tricolor L.). This vegetable plant is commonly consumed as food due to its nutritional content and numerous health benefits. To cultivate amaranth on salinity-stressed land, additional nutrients are require… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…Pelinganga [45] also showed that NPK fertilisers improve the chlorophyll content and yield of Amaranthus hybridus. This assertion was corroborated by [46], who observed improved growth and chlorophyll content in Amaranthus tricolor. The elicitors significantly influenced the chlorophyll content of Amaranthus cruentus with the highest chlorophyll content when compared to the control obtained in plants treated with SA250 (Table 2).…”
Section: Chlorophyll (Spad)supporting
confidence: 56%
“…Pelinganga [45] also showed that NPK fertilisers improve the chlorophyll content and yield of Amaranthus hybridus. This assertion was corroborated by [46], who observed improved growth and chlorophyll content in Amaranthus tricolor. The elicitors significantly influenced the chlorophyll content of Amaranthus cruentus with the highest chlorophyll content when compared to the control obtained in plants treated with SA250 (Table 2).…”
Section: Chlorophyll (Spad)supporting
confidence: 56%
“…These findings were attributed due to the negative correlation between the Cd content-a toxic element to plants-and the observed changes in diameter. Moreover, salinity and biofertilizers can also modulate the metaxylem diameter of Amaranthus tricolor stem [23].…”
Section: Discussionmentioning
confidence: 99%
“…The application of BF in wheat seedlings lessened the negative effects of salinity by increasing chlorophyll content and decreasing proline content, and improved plant growth and yield [ 28 , 37 ]. Under salt stress, amaranth enhanced plant height and biomass production [ 101 ]. It has also been reported that the application of BF to lavender enhanced its capacity to withstand salt stress by increasing morphological attributes and RWC, Chl a, Chl b, and total Chl content as well as its essential oil output [ 102 ].…”
Section: Organic Amendments For Salinity Stress Mitigationmentioning
confidence: 99%